Return to work rates and activity profiles: are there differences between those receiving C-ADR and ACDF? - Traynelis, Vincent C; Leigh, Barbara C; Skelly, Andrea C (Evidence-Based Spine-Care Journal, 2012)
Study design: Comparative effectiveness review.Study rationale: The ability of a patient to return to work and the speed with which this occurs are important outcome metrics for the assessment of patients undergoing spinal surgery.Clinical questions: In patients with degenerative disease of the cervical spine, does cervical artificial disc replacement (C-ADR) lead to better work-related outcomes than fusion? Does return to work after surgery differ based on gender, age, smoking, litigation status, workers’ compensation status, or other sociodemographic factors?Methods: A systematic search and review of the English-language literature was undertaken to identify studies published through October 2, 2011. PubMed, Cochrane, National Guideline Clearinghouse Databases, and bibliographies of key articles were searched. Two individuals independently reviewed articles based on inclusion and exclusion criteria, which were set a priori. Each article was evaluated using a predefined quality-rating scheme.Results: For follow-up periods of more than 6 months, there was no significant difference in work status between disc replacement and fusion patients; however, C-ADR patients began working sooner after surgery. Statistical significance for earlier return was not reached in all studies.Conclusions: Most patients undergoing cervical decompression and fusion or C-ADR return to work. The rates are equivalent at 6 months but patients treated with C-ADR resumed work sooner.